Intraepithelial alterations in the Guinea pig lateral prostate at different ages after estradiol treatment - Scarano, W. R.; Cordeiro, R. S.; Góes, R. M. [UNESP]; Taboga, S. R. [UNESP] (My University, 2004)
The prostate is an accessory gland of the mammal reproductive system with great volume and high functional importance. Many works infer that, in addition to the androgenic ones, the estrogen can be associated with benign prostatic hyperplasia and prostatic cancer, but no conclusive evidence exists on the role of estrogen in normal prostatic and neoplastic tissue. The objective of this work was to evaluate the effects of chronic administration of estradiol benzoate on the lateral prostate of guinea pigs in the pre-pubescent, pubescent, post-pubescent and adult phases, with emphasis on the modifications provoked by this hormone on the glandular epithelium. The analyses of the estradiol-treated and control groups were investigated using histological procedures and transmission electron microscopy. The histopathological analysis of the lateral prostate in the treated group revealed areas where epithelial dysplasia was observed, assuming at some places a pattern of epithelial stratification characteristic of prostatic intraepithelial neoplasia. After ultrastructural analysis, the following were observed: enlargement of the internal membranes, heterogeneity in the cellular types, hypertrophy of the basal cells and apparent decrease of cytoplasmic organelles in some cells of the prostatic intraepithelial neoplasia. Still, a loss of cellular polarity was observed, along with nuclei of various forms, sizes and heights - as well as irregular chromatin distribution patterns. Such alterations were found mainly in pubescent, post-pubescent and adult animals subject to the chronic administration of estradiol. These findings reinforce the already existent data in understanding the role of estrogen in the etiology of prostatic diseases.
Keywords: Epithelium; Estradiol; Guinea pig; Hyperplasia; Prostate; estradiol; animal experiment; animal model; animal tissue; cell type; chromatin; controlled study; developmental stage; guinea pig; histology; histopathology; nonhuman; prostate epithelium; transmission electron microscopy; Aging; Animals; Animals, Newborn; Epithelial Cells; Guinea Pigs; Male; Microscopy, Electron, Transmission; Prostatic Intraepithelial Neoplasia; Prostatic Neoplasms; Sexual Maturation; Animalia; Cavia; Cavia porcellus; Mammalia; Sus scrofa